Profiles of multiple intelligences among a sample of primary school teachers in Minya, Egypt - Abd AL Haleim, Reda Rabie Abdel (Journal of Educational and Psychological Sciences, 2021)
This study aims at identifying the level of multiple intelligences (linguistic- logical/mathematical- spatial- motor- musical- interpersonal- social- natural- existential) among primary school teachers. It also aims at revealing the multiple intelligences profiles according to gender (male- female). The study used the descriptive method, and for data collection, the researcher applied the multiple intelligences scale (prepared by the researcher. The research sample comprised of (218) primary school teachers. Results demonstrated that the degree of intelligences) logical/mathematical- spatial- interpersonal- social- motor existential (by primary school teachers was high while the (linguistic – social- natural- musical intelligences) possession level was medium besides, existential intelligence was in the first order of multiple intelligences profiles for both males and females, while the order of other intelligences differed between both genders. In light of the research results, recommendations and further suggestions for raising and developing the level of multiple intelligences of teachers were presented.
Keywords: multiple intelligences; teachers; profiles